2015
DOI: 10.1074/jbc.m115.664169
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum (ER) Stress Induces Sirtuin 1 (SIRT1) Expression via the PI3K-Akt-GSK3β Signaling Pathway and Promotes Hepatocellular Injury

Abstract: Sirtuin 1 (SIRT1), an NAD؉ -dependent histone deacetylase, plays crucial roles in various biological processes including longevity, stress response, and cell survival. Endoplasmic reticulum (ER) stress is caused by dysfunction of ER homeostasis and exacerbates various diseases including diabetes, fatty liver, and chronic obstructive pulmonary disease. Although several reports have shown that SIRT1 negatively regulates ER stress and ER stress-induced responses in vitro and in vivo, the effect of ER stress on SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 36 publications
3
57
0
Order By: Relevance
“…In addition, the downregulation of OGFRP1 has been revealed to inhibit hepatocellular carcinoma via the regulation of AKT/mTOR and Wnt/b-catenin signals [19]. Koga et al pointed out that the PI3K/AKT/GSK-3b signals is crucial to SIRT1 induction by stress reaction of endoplasmic reticulum and consequently regulates hepatocellular injury [38]. In this study, suppression of OGFRP1 restrained the activation of PI3K/AKT/GSK-3b signals in the Ishikawa cells, which was neutralized after inhibition of miR-124-3p, and further the concurrent inhibition of OGFRP1 inhibited this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the downregulation of OGFRP1 has been revealed to inhibit hepatocellular carcinoma via the regulation of AKT/mTOR and Wnt/b-catenin signals [19]. Koga et al pointed out that the PI3K/AKT/GSK-3b signals is crucial to SIRT1 induction by stress reaction of endoplasmic reticulum and consequently regulates hepatocellular injury [38]. In this study, suppression of OGFRP1 restrained the activation of PI3K/AKT/GSK-3b signals in the Ishikawa cells, which was neutralized after inhibition of miR-124-3p, and further the concurrent inhibition of OGFRP1 inhibited this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We further demonstrated that USP22 restrained thyroid cancer cell apoptosis by enhancing SIRT1 deubiquitination, and SIRT1 could also decrease cell apoptosis through FOXO3a deacetylation-induced PUMA repression. SIRT1 is an NAD(+)-dependent histone deacetylase and implicated in several biological processes such as senescence, stress reaction and cell survival [34]. SIRT1 deubiquitination is crucial to its function in cell apoptosis and survival in response to DNA damage [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (35) identified that downregulating Smad3/ATF4 is essential for the SIRT1 suppression of ER stress-induced apoptosis. Furthermore, Koga et al (36) reported that ER stress promotes hepatocellular injury via increasing the expression of SIRT1 in the PI3K/Akt-GSK3β signalling pathway. Prola et al (37) demonstrated that SIRT1 attenuates ER stress-induced cell apoptosis in cardiomyocytes via eIF2a deacetylation.…”
Section: Discussionmentioning
confidence: 99%